Epidemiology of aminoglycosides resistance and phenotypic detection of aac(6′)-Ib-cr gene in ESBL-producing Enterobacterales in febrile urinary tract infection in children - Audrey Baron; Fouad Madhi; Philippe Bidet; Corinne Levy; Robert Cohen; Yasmine Benhadid-Brahmi; Camille Jung; Elsa Sobral; Kevin La; Stéphane Bonacorsi; André Birgy (Journal of Global Antimicrobial Resistance, 2025)
Objectives: ESBL-producing Enterobacterales (ESBL-E) poses a growing challenge in managing febrile urinary tract infections (FUTIs) in children, leaving amikacin as a good probabilistic once-daily and outpatient treatment option. This epidemiological study investigates aminoglycoside resistance patterns among pediatric ESBL-E isolates, with a particular focus on the aac(6′)-Ib-cr gene – a common resistance determinant that elevates amikacin MICs and may compromise its efficacy. We also aimed to evaluate a phenotypic method to detect aac(6′)-Ib-cr in clinical practice. Methods: We studied 251 ESBL-E from pediatric FUTIs collected in 24 centers. All underwent whole-genome sequencing to determine aminoglycoside resistance genes. Antimicrobial susceptibility was determined by disk diffusion and E-test. Amikacin MICs were measured at standard (10^5 CFU/mL) and high (10^7 CFU/mL) inocula, and interpreted according to EUCAST 2024 breakpoints. Results: Clinically relevant aminoglycoside-resistance genes were identified in 54.2% of isolates, although only 3.6% were resistant to amikacin. Among the isolates, 31.1% (78/251) carried aac(6′)-Ib-cr, co-occurring with other aminoglycoside-resistance genes in 94.9% of cases. Strains harboring aac(6′)-Ib-cr displayed higher amikacin MICs (median 8 mg/L vs 2 mg/L; P < 0.001) and became resistant at high inoculum. We propose a simple phenotypic algorithm combining “cliff-like” amikacin inhibition-zone edges and tobramycin disk diameters (<16 mm), correctly identifying 99% of our aac(6′)-Ib-cr-positive strains. Conclusion: The low amikacin resistance in ESBL-E supports its continued use as a reliable empiric treatment for pediatric FUTIs. However, the aac(6′)-Ib-cr gene can raise amikacin MICs, potentially compromising efficacy in high-inoculum infections despite EUCAST susceptibility. Our phenotypic algorithm helps detect it and guide treatment decisions for pediatric FUTIs.